The Importance of Being a Flaneur:: An Introduction to the Thought of Nassim Nicholas Taleb - Cunha, Martim Vasques da (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
This article is an introduction to philosophical thinking of the Lebanese essayist Nassim Nicholas Taleb, exposing the key concepts of his work, especially the Black Swan and “AntiFragile”, and relating them to the reflections on uncertainty made by Ludwig von Mises (in particular in his book Human Action) and the idea of “Spontaneous Order” elaborated by Friedrich von Hayek.